Management Tools for Underground Mining Optimization (SCIÉNDO INGENIUM, 2024)
The objective of this research work was to optimize productivity and reduce costs in mechanized underground mining operations; for which management tools such as TPM (Total Productive Maintenance) were applied, which made it possible to ensure the expected reliability of the equipment and Management Indicators (KPIs), contributing to greater effectiveness in operations and statistical tools to improve quality, Pareto charts and Ishikawa diagrams. A descriptive methodology consisting of the daily collection of data contained in the mine operations records, to analyze it and identify opportunities for improvement in each process, thus determining unproductive delays in drilling, ore cleaning and hauling. Among the results, it was identified that the availability of the H 357 drilling equipment had an increase of 6.80% after implementing management tools. It was also evident that productivity increased considerably in the effective working time of the Scoop measured in tons/hour, thanks to the implementation of TPM, from 79.90 to 85. Ultimately, the application of management tools allowed a philosophical change within the organization, guiding a more effective management of operations of the mining company.
Keywords: Total Productive Maintenance; Key Performance Indicator; Productivity; Statistical tools; Costs